Media as site of social struggle the role of Philippine radio and television in the EDSA Revolt of 1986 - Enriquez, Elizabeth L. (2006)
The media are an arena of social and political contention. While they are more often regarded as a force for the status quo, they also have the potential to arm their audiences with information these audiences need to effect change. The liberative potential of the mass media is enhanced by the growth of media technology, which, while enforcive of the rule of the dominant forces in society, also has the potential to empower forces challenging the status quo. For its capacity to transcend geographical and political boundaries, broadcasting is particularly crucial during crisis situations. By sending information virtually to any audience within technological reach in real time, television and radio create an immediate impact on public understanding, perception and opinion as a crisis unfolds and demands citizen response and reaction, thus helping mobilize the critical mass change requires. This was most tellingly and dramatically demonstrated during the 1986, or first EDSA revolt, when the broadcast media played a significant part in bringing Filipinos in their millions out into the streets to overthrow the Marcos dictatorship.
Includes bibliographical references (pages 136-138).